Maximizing Profit Growth: How Net Profit Margin And Return On Assets Interact With Firm Size - Erisa Aprilia Wicaksari; Kris Brantas Abiprayu; Angga Pandu Wijaya; Bogy Febriatmoko; Tiara Yulianti (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to analyze the effect of net profit margin and return on assets on profit growth by adding firm size as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange. The population in this study comprises property and real estate companies listed on the Indonesia Stock Exchange from 2019 to 2023. The sampling technique is determined using purposive sampling based on criteria set by the researchers, resulting in a sample of 52 property and real estate companies. Panel data regression and moderated regression analysis (MRA) are used to analyze the data. The results of this study indicate that the net profit margin variable does not affect profit growth, while return on assets has a significant effect on profit growth. Furthermore, firm size can moderate the effect of net profit margin on profit growth. However, firm size cannot moderate the effect of return on assets on profit growth. Based on the results of this study, it is expected that future researchers can add other factors that may influence profit growth. In selecting moderating variables, it is hoped that future researchers will choose appropriate moderating variables to strengthen profit growth.